Are unimanual movements bilateral?. (June 2020) - Chettouf, Sabrina; Rueda-Delgado, Laura M.; de Vries, Ralph; Ritter, Petra; Daffertshofer, Andreas
Highlights: Bilateral neural interactions, excitatory and inhibitory, are present across the motor network during unimanual movements. An increase in task difficulty requires more efficient communication between hemispheres. Anatomical properties of transcallosal fiber tracts enable essential interhemispheric information exchange. Left (pre)motor areas play a key role in complex motor tasks. Abstract: Motor control is a fundamental challenge for the central nervous system. In this review, we show that unimanual movements involve bi-hemispheric activation patterns that resemble the bilateral neural activation typically observed for bimanual movements. For unimanual movements, the activation patterns in the ipsilateral hemisphere arguably entail processes that serve to suppress interhemispheric cross-talk through transcallosal tracts. Improper suppression may cause involuntary muscle co-activation and as such it comes as no surprise that these processes depend on the motor task. Identifying the detailed contributions of local and global excitatory and inhibitory cortical processes to this suppression calls for integrating findings from various behavioral paradigms and imaging modalities. Doing so systematically highlights that lateralized activity in left (pre)motor cortex modulates with task complexity, independently of the type of task and the end-effector involved. Despite this lateralization, however, our review supports the idea of bi-hemispheric cortical activation being a fundamental mode of upper extremity motor control.